Crystal Structure of Regularly Th‐Symmetric [U(NO3)6]2− Salts with Hydrogen Bond Polymers of Diamide Building Blocks. (5th December 2018) - Takao, Koichiro; Kazama, Hiroyuki; Ikeda, Yasuhisa; Tsushima, Satoru
Abstract: Hexanitratouranate(IV), [U(NO3 )6 ] 2−, has been crystallized with anhydrous H + ‐involving hydrogen bond polymers connected by selected diamide building blocks. Thanks to the significant moderation of electrostatic interactions between the anions and cations, the molecular structure of [U(NO3 )6 ] 2− in these compounds is regularly Th ‐symmetric. The f–f transitions stemming from 5f 2 configuration of U 4+ are strictly forbidden by the Laporte selection rule in such a centrosymmetric system, so that the obtained compounds are nearly colourless in contrast to other U IV species usually coloured in green.